Unlocking engagement: exploring the drivers of elderly participation in digital backfeeding through community education - Sijie Sun (Frontiers in Psychology)
Amid China’s rapid aging and digitalization, elderly individuals face a “digital refugee” dilemma, making community education a vital channel for enhancing their digital participation. To address this, the study investigates how community education influences elderly engagement in digital backfeeding—a process where younger generations assist older adults with digital skills—by examining the interplay of personal, technological, and community factors in promoting technology acceptance. Using an integrated framework of the UTAUT, TTF, and TAM models, the research surveyed 482 elderly participants in community centers in Taiyuan, China, focusing on variables such as task and technology characteristics, social influence, facilitating conditions, perceived usefulness, ease of use, and technology anxiety. Analysis through AMOS and SPSS Process macro revealed that task characteristics significantly enhance engagement willingness, although technology characteristics introduce certain challenges. Furthermore, social influence and facilitating conditions were found to positively affect willingness and behavior, mediated by perceived usefulness, ease of use, and technology anxiety. Notably, participatory digital skills exhibited a stronger moderating effect on engagement willingness compared to receptive skills. These findings underscore the pivotal role of community education in fostering digital inclusion among the elderly. Practical recommendations include simplifying technology interfaces, creating supportive environments, and prioritizing participatory skills development to enhance technology acceptance, offering valuable insights for the design of age-friendly digital tools that bridge the digital divide.